BMP Regulation of Myogenesis in Zebrafish - Patterson, Sara E. (2010)
In amniotes, BMP signaling from lateral plate and dorsal neural tube inhibits differentiation of muscle precursors in the dermomyotome. Here, we show that BMPs are expressed adjacent to the dermomyotome during and after segmentation in zebrafish. In addition, downstream BMP pathway members are expressed within the somite during dermomyotome development. We also show that zebrafish dermomyotome is responsive to BMP throughout its development. Ectopic overexpression of Bmp2b increases expression of the muscle precursor marker pax3, and changes the time course of myoD expression. At later stages, overexpression increases the number of Pax7+ myogenic precursors, and delays muscle differentiation, as indicated by decreased numbers of MEF2+ nuclei, decreased number of multi-nucleated muscle fibers, and an increased myotome angle. In addition, we show that while BMP overexpression is sufficient to delay myogenic differentiation, inhibition of BMP does not detectably affect this process, suggesting that other factors redundantly inhibit myogenic differentiation.